Deficiencies of nitrogen, calcium, and micronutrients are the most limiting factors for growth and yield of smell pepper plants - da Silva Magalhães, Deila; Matos Viegas, Ismael de Jesus; da Silva Barata, Henrique; Costa, Milton Garcia [UNESP]; da Silva, Bianca Cavalcante [UNESP]; de Lima Mera, Willian Yuki Watanabe (FapUNIFESP (SciELO), 2023)
Cultivation and commercialization of Capsicum pepper have great importance in Brazil. This work assessed the influence of omission of macro and micronutrients on the growth and mineral nutrition of sweet pepper plants (Capsicum chinense Jacquin). The research was carried out in a greenhouse with washed sand as substrate. The experimental design was completely randomized with five replications and eight treatments: complete (control), omission of N, P, K, Ca, Mg, S, and micronutrients (B, Cu, Fe, Mn and Zn). The plants were submitted to the treatments when they reached an average height of 20 cm and the nutrient solution was supplied by percolation in plastic pots and renewed every 15 days. Nutrients omission affected negatively plant growth as a whole. The omission of N, Ca, and micronutrients greatly reduced sweet pepper yield. The C. chinense plants presented the sequence by dry matter production of shoots and roots in descending order: COMP > OP > OS > OK > Omg > ON > Oca > OMicro.
Keywords: Capsicum chinense Jacquin; nutrient export; omission of nutrients